Safety and efficacy of a wireless pulmonary artery pressure sensor: primary endpoint results of the SIRONA 2 clinical trial. (10th June 2022) - Sharif, Faisal; Rosenkranz, Stephen; Bartunek, Jozef; Kempf, Tibor; Assmus, Birgit; Mahon, Niall G.; Mullens, Wilfried
Abstract: Aims: Implantable pulmonary artery pressure (PAP) sensors have been shown to reduce heart failure hospitalizations (HFH) in selected patients. The goal of this study was to evaluate the safety and efficacy of a novel wireless PAP monitoring system in patients with heart failure (HF). Methods and results: This is a prospective, multi‐centre, open‐label, single‐arm trial evaluating the safety and efficacy of the Cordella™ PA Sensor System including the comprehensive Cordella™ Heart Failure System (CHFS) in patients with New York Heart Association (NYHA) Class III heart failure with a heart failure hospitalization and/or increase of N‐terminal pro‐Brain Natriuretic Peptide (NT‐proBNP) within 12 months of enrolment. The primary efficacy endpoint was the accuracy of PA sensor mean PAP measurements, compared with fluid‐filled catheter mean PAP measurements obtained by standard right heart catheterization (RHC) at 90 days post‐implant, assessed in all patients with a successful implant. The primary safety endpoint was freedom from adverse events associated with use of the Cordella PA Sensor System through 30 days post‐implant, assessed in all patients who entered the cath lab for PA sensor implant. The PA sensor was successfully implanted in 70 patients. Equivalence between the PA sensor and RHC for mean pulmonary artery pressures was excellent with measurements confined within the equivalence bounds of −4.0 to 4.0 mmHg (mean PAP: 0.0 to 2.9 mmHg, P = 0.003). The device safety profile was excellent with 98.6% freedom from Device System Related Complications, defined as invasive treatment, device explant or death. There were no pressure sensor failures. Patients' adherence to daily measurement transmissions of PAP and vital signs was 94%. Conclusions: This trial supports the safety and efficacy of the Cordella PA Sensor System and in conjunction with the CHFS enables comprehensive HF management in NYHA class III heart failure patients.